2011
DOI: 10.1007/s11120-011-9622-8
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput pyrosequencing of the chloroplast genome of a highly neutral-lipid-producing marine pennate diatom, Fistulifera sp. strain JPCC DA0580

Abstract: The chloroplast genome of the highly neutral-lipid-producing marine pennate diatom Fistulifera sp. strain JPCC DA0580 was fully sequenced using high-throughput pyrosequencing. The general features and gene content were compared with three other complete diatom chloroplast genomes. The chloroplast genome is 134,918 bp with an inverted repeat of 13,330 bp and is slightly larger than the other diatom chloroplast genomes due to several low gene-density regions lacking similarity to the other diatom chloroplast gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…We also identified 135 chloroplast genes and 31 mitochondrial genes (the chloroplast genes were previously reported [Tanaka et al, 2011]). No homoeologous gene pairs were found in the mitochondrial or chloroplast genomes.…”
Section: Genome Sequencing and Assemblymentioning
confidence: 94%
See 1 more Smart Citation
“…We also identified 135 chloroplast genes and 31 mitochondrial genes (the chloroplast genes were previously reported [Tanaka et al, 2011]). No homoeologous gene pairs were found in the mitochondrial or chloroplast genomes.…”
Section: Genome Sequencing and Assemblymentioning
confidence: 94%
“…The scaffolds were assembled with LASTZ and LALIGN to yield a draft genome sequence corresponding to 24.8-fold redundant sequence coverage. At this stage, a chloroplast genome (135 kb) (Tanaka et al, 2011) and a mitochondrial genome (>38.6 kb) were identified; however, we failed to determine the chromosome structures from the alignment blocks in the draft nuclear genome.…”
Section: Genome Sequencing and Assemblymentioning
confidence: 99%
“…However, in most diatom species, existence of different rbcL variants, their inheritance and copy number, and also the number of chloroplasts per cell, is not well investigated. Chloroplast genome sequencing studies on diatoms have indicated the presence of only one rbcL copy in some centric and pennate diatoms (Kowallik et al 1995;Oudot-Le Secq et al 2007;Tanaka et al 2011), but have not been established in other diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…JPCC DAO0580 (Tanaka et al 2011). Additionally, the plastid genomes of two dinoflagellates Kryptoperidinium foliaceum and Durinskia baltica, also known as dinotoms because they harbouring a diatom endosymbiont, were sequenced recently (Imanian et al 2010).…”
Section: Introductionmentioning
confidence: 99%